DETEKSI DINI SKOLIOSIS PADA SISWI KELAS 3 DI SDIT AR RISALAH KARTASURA - Kurniati, Risa Fitri; Annisa, Nur; Sugiyarti, Zara; Hafizh, Babsell Aufaa; Jannah, Amala Istiqomah; Widodo, Agus; Pristianto, Arif; Rahman, Farid (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
Scoliosis is a spinal disorder where the spine bends to the side (lateral curvature) forming the letter 'S' or 'C' and can be seen when the curvature gets worse and causes discomfort. Untreated scoliosis can get worse, affecting cardiopulmonary function, limiting mobility for sufferers and having a negative impact on body posture. Early detection of scoliosis plays an important role in preventing the deformity and damage from getting worse. Based on age groups, idiopathic scoliosis can be grouped into four, namely infantile (0-3 years). juvenile (4-9 years), adolescent (10 years until growth stops). and adult (>19 years). The purpose of this activity is to prevent potential progression of deformity and early detection of severe deformity that requires operative correction. The basic method of scoliosis screening is a clinical examination in a forward-bending position using a scoliometer which can also be used in a standing or sitting position. Scoliometer measures the Angle of Trunk Rotation. The results of the counseling show that there are several grade 3 students who experience scoliosis. Scoliosis causes participants to experience physical impacts such as a degree of tilt in the spine. The conclusion of this education and counseling on early detection of scoliosis has had a good impact in helping to increase knowledge in grade 3 students at SDIT Ar Risale Kartasura.